Den svårfångade kronologin: Om gravstratigrafi och problem med dateringen av Sigtunas tidigmedeltida kyrkor - Wikström, Anders (Hikuin, 2006)
The elusive chronology Interpreting stratigraphy in graves and the problems with dating the early medieval churches in Sigtuna By Anders Wikström Sigtuna is the oldest medieval town in Sweden. It was founded around 970-980 by king Erik Segersäll and was from the very beginning characterized by a strong Christian influence. The construction of stone churches took place early. The oldest stonechurch was built in the second half of the eleventh century. It is uncertain how many churches there were in Sigtuna during the Middle Ages. Out of the original 8-11 medieval churches and ecclesiastical institutions only four are still visible today three are ruins. One has been discovered as a result of archaeological excavations, and another two or three possible church sites are known through their cemeteries. Some of the churches are mentioned in medieval written records, but are not yet discovered. This article is an attempt to shed light upon the problems with dating the early medieval churches in Sigtuna. In spite of intens periods of archaeological excavations over more than a hundred years there are still uncertainty about the datings of the individual churches. This is first and foremost a result of the fact that few archaeological excavations have been carried out inside the churches. Therefore most of the dating proposals are based upon architectural styles and elements. Extensive modern land development on the former churchyards have led to more than 700 graves having been excavated. Data from about 570 of these have been processed and studied for a PhD in osteology. One question asked in the article is if it is possible to use grave material to indirectly date the churches. The number of burials and the distribution of arms positions in the burials differ between the three churchyards in the study, maybe because the churchyards have different datings. The result may also be due to different burial practices. In the article there is also a presentaion of a method that will be tested in the near future. The method is in short a test to see if a number of C14 samples from graves in conjunction with archaeological results can be used to calculate more precise statistical results from the samples. The expected result is that this method will work and thereby improve and increase the possibilities to get more presice datings of the individual stone churches.